Antibacterial effect of cotton fabric treated with silver nanoparticles of different sizes and shapes - KHE Yunusov; SV Mullajonova; АА Sarymsakov; JZ Jalilov; FM Turakulov; SSH Rashidova; Renat Letfullin (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2019)
Stable silver Nanoparticles in solutions of sodium-carboxymethylcellulose (Na-CMC) were synthesized, and their structure and physico-chemical properties were studied. The form and sizes of silver nanoparticles formed in solutions of CMC and cotton fabrics were studied using UV-VIS spectroscopy, atomic force microscopy and transmission electron microscopy methods. It was found that the silver nitrate concentration increase in sodium carboxymethylcellulose solutions, as well as photoirradiation of the hydrogel lead to the changes of the silver nanoparticles size and shape. Investigations have shown that spherical silver nanoparticles with sizes of 5-35nm and content of 0.0086 mass% in cotton fabrics possess high bactericidal activity. Stabilization of silver nanoparticles has preserved bactericidal and bacteriostatic activities during the washing of cotton fabrics and textiles on their base.